The "Egerton Gospel" (Egerton Papyrus 2 + Papyrus Köln VI 255): introduction, critical edition, and commentary - Zelyck, Lorne R. (Texts and editions for New Testament study, 2019)
Front Matter -- Copyright Page -- Dedication -- Preface -- Introduction -- The Acquisition and Publication of the Egerton Gospel Fragments -- A Description of the Fragments -- Transcription, Reconstruction, and Translation -- A Confrontation with the Authorities (EG 1v.1–26 [P. Eg. 2, 1v.1–20 + P. Köln 255, 1v.1–6<]) -- An Attempt to Stone and Arrest Jesus (EG 1r.1–10 [P. Eg. 2, 1r.1–10]) -- The Healing of a Leper (EG 1r.11–24 [P. Eg. 2, 1r.11–20 + P. Köln 255, 1r.1–7]) -- Jesus’ Strange Question (EG 2v.1–5 [P. Eg. 2, 2v.1–5]) and the Miracle on the Jordan River (EG 2v.6–16 [P. Eg. 2, 2v.6–16]) -- The Question of Tribute (EG 2r.1–18 [P. Eg. 2, 2r.1–17<]) -- An Unidentified Text (EG 3v.1–6 [P. Eg. 2, 3v.1–6]) -- Another Attempt to Stone Jesus (EG 3r.1–6 [P. Eg. 2, 3r.1–6]) -- Conclusion -- Back Matter -- Word Statistics -- Synoptic Charts of Parallel Passages -- Bibliography -- Indexes.